In Vivo Characterization of Carotid Neointimal Hyperplasia by use of Optical Coherence Tomography: Before and After Cutting Balloon Angioplasty. Issue 6 (20th February 2015) - Blackham, Kristine A.; Kim, Benny S.; Jung, Richard S.; Badve, Chaitra; Manjila, Sunil; Sila, Cathy A.; Bambakidis, Nicholas C.
ABSTRACT Optical coherence tomography (OCT) is a modern intravascular imaging modality that has the capability to provide detailed, in vivo characterization of the arterial wall and atherosclerotic plaque. The current understanding of the appearance of atherosclerotic plaque via OCT is largely based on coronary arterial studies where OCT information has been employed to guide therapeutic management and permits the immediate evaluation of percutaneous intervention. The clinical success of OCT in the coronary arteries has laid the foundation for investigation of the carotid artery and thus, stroke risk assessment. We report the novel use of OCT for tissue characterization of severe stenosis subsequent to carotid artery stenting (CAS), both before and after treatment with cutting balloon angioplasty.